Nedw - Davies, E. Tegla (Edward Tegla), 1880-1967; Illingworth, Leslie Gilbert, 1902-1979 (Salt Lake City, UT : Project Gutenberg, 2022)
"Nedw" by E. Tegla Davies is a novel written in the early 20th century. The story centers on the adventures and experiences of a young boy named Nedw, along with his cousin Wmffre, as they navigate childhood escapades in a rural Welsh setting. The narrative vividly captures the innocence and curiosity of youth, exploring themes of friendship, mischief, and the joys of exploration. The opening of the book introduces us to Nedw and Wmffre on a typical afternoon as they discuss skipping school to go nut-gathering instead. The chapter paints a nostalgic picture of their carefree childhood, full of humorous exchanges and mischievous plans. As they encounter their teacher, Joseph, and navigate school-related challenges, Nedw's personality and dynamics with others, including his fondness for fun and adventure, begin to emerge. This lively introduction sets the stage for a series of escapades that promise to engage readers with tales of laughter, mischief, and poignant moments from childhood. (This is an automatically generated summary.)
Release date is 2022-02-17
Mardi Desjardins & the online Distributed Proofreaders Canada team at https://www.pgdpcanada.net
Keywords: Boys -- Juvenile fiction; Children's stories, Welsh